The vacuum interrupter theory, design, and application - Slade, Paul G. (CRC Press, Taylor & Francis Group, 2008)
Drawn from the author's more than four decades of practical experience in the industry, this book first discusses the design and manufacture of the vacuum interrupter before delving into its general application. With extensive references in each chapter for further exploration, this comprehensive guide provides essential, up-to-date knowledge to understand fully this vital technology.